Mental health of the elderly: perceptions related to aging - Soares Vello, Lais; Pereira, Maria Alice Ornellas [UNESP]; Popim, Regina Célia [UNESP] (Investigación Y Educación En Enfermería, 2014)
To understand the elderly's perception of their current condition. Methodology. Study undertaken in 2012 using the qualitative method of Minayo and the thematic analysis according to Bardin's suggestions. Data were collected through semi-structured interviews that took place in the homes of the elderly people. The guiding question was: At this point in your life, how do you feel? Tell me. Results. The elderly who were satisfied stated that this was due to the good relationship with their family, spouse, to the fact of having autonomy and respect from the society. Those who were shown to be dissatisfied reported lack of family support, physical limitations imposed by age and the presence of illnesses as the main causes. Conclusion. The adult population requires the use of care technologies that cover all the stages of life, including old age. Nursing professionals should be prepared for the increasing care demand of these people.

Comprender cómo el anciano percibe su condición en ese momento de su vida. Metodología. En 2012 se realizó un estudio en el que se empleó el método cualitativo, según Minayo, y se hizo análisis temático de acuerdo las indicaciones sugeridas por Bardin. La información fue recolectada de entrevistas semiestruturadas realizadas en las viviendas de los ancianos. La pregunta orientadora fue: ¿cómo se siente en este momento de su vida? Cuénteme. Resultados. Los ancianos satisfechos atribuyeron ese sentimiento a la buena convivencia con la familia, con el cónyuge, al hecho de tener autonomía y respeto por parte de la sociedad. Los que se mostraron insatisfechos, relataron falta de apoyo de la familia, limitaciones físicas propias de la edad y la presencia de enfermedades. Conclusión. La población adulta exige para su atención la utilización de tecnologías de cuidado que contemple todas las etapas de la vida, incluyendo la vejez. Los profesionales de enfermería deben estar preparados para la creciente demanda de cuidado de estas personas.

Compreender como o ancião percebe sua condição nesse momento da sua vida. Metodologia. Em 2012 se realizou um estudo no que se empregou o método qualitativo segundo Minayo e se fez análise temática segundo as indicações sugeridas por Bardin. A informação foi coletada de entrevistas semiestruturadas realizadas nas moradias dos anciãos. A pergunta orientadora foi: Neste momento da sua vida, como se sente? Conte-me. Resultados. Os anciãos satisfeitos atribuíram esse sentimento à boa convivência com a família, com o cônjuge, ao fato de ter autonomia e respeito da sociedade. Os que se mostraram insatisfeitos relataram falta de apoio da família, limitações físicas próprias da idade e a presença de doenças como principais queixas. Conclusão. A população adulta exige para seu atendimento a utilização de tecnologias de cuidado que contemple todas as etapas da vida, incluindo a velhice. Os profissionais de enfermagem devem estar preparados para a crescente demanda de cuidado destas pessoas.
Salud mental del anciano: percepciones relacionadas con el envejecimiento
Saúde mental do Idoso: percepções relacionadas ao envelhecimento
Keywords: Aged; Mental health; Primary health care; Qualitative research; Anciano; Salud mental; Atención primaria de salud; Investigación cualitativa; Idoso; Saúde mental; Atenção primária à saúde; Pesquisa qualitativa